PAXTA TO‘QIMACHILIK KLASTER ISHTIROKCHILARI OʻRTASIDAGI IQTISODIY MUNOSABATLAR TAHLILI (Marketing Journal, 2026)
AbstractThis article analysed the theoretical foundations and practical aspects of economicrelations among cluster participants. The study examined the impact of cluster systemson production efficiency, resource exchange, innovative cooperation, andcompetitiveness. The theoretical approaches of Porter, Krugman, and Marshall weresystematically reviewed. Using Uzbekistan’s cotton-textile clusters as a case study, theinfluence of vertical and horizontal integration on production volume, exportperformance, and employment was evaluated based on statistical data. The analysisdemonstrated improved industrial efficiency under cluster-based productionorganization. The findings confirmed that the development of intra-cluster economicrelations strengthened value chains, increased industrial productivity, and expandedexport capacity. The results were assessed as an analytical basis for improvingeconomic cooperation among cluster participants.Keywords: cluster, economic relations, competitiveness, vertical integration,horizontal integration, innovation, value chain, textile industry, export.